Watching SERS glow for multiplex biomolecular analysis in the clinic: A review. (June 2019) - Zeng, Yi; Koo, Kevin M.; Trau, Matt; Shen, Ai-Guo; Hu, Ji-Ming
Graphical abstract: Highlights: Multiplex biomarker panels are facilitating modern comprehensive disease detection. Indirect SERS technique is highly attractive for multiplex biomolecular analysis. More research focusing on Raman reporter developments will be ideal for SERS advancement. Accurate biomolecule measurement is achievable through various SERS quantification modes. Significant challenges need to be resolved for SERS clinical translation. Abstract: Surface-enhanced Raman spectroscopy (SERS) has been widely recognized as a powerful and promising technique for biomedical applications due to its (i) abundant intrinsic spectral fingerprint information, (ii) excellent detection sensitivity, and most importantly, (iii) outstanding multiplexing potential owing to unique narrow spectral widths. Recent advances in nano-synthesis of innovative SERS substrates, along with emergence of novel Raman reporters, have provided tremendous improvement for multiplex biomolecular analysis in complex biological systems. Particularly, there has been considerable momentum on numerous exciting multiplex SERS-based disease approaches through modern liquid biopsy sensing and cellular tissue imaging advancements. Yet, proceeding on from highly-promising proof-of-concept work in laboratory research, a vacuum still exists in the successful clinical translation of the aforesaid multiplex SERS platforms to realize real-world use. To fuel the promising glow of SERS towards clinical translation, this review summarizes the recent cutting-edge progress on novel multiplex SERS strategies for biomolecular analysis, and discusses the existing challenges around clinical translation. This is accompanied by our insights on how to improve practical use, aiming to propose directions on the incorporation of SERS into clinical use.